The Sociology of Scientific Exegesis: Tafsir Al-Jawāhir and the Formation of a Muslim Middle-Class Scientific Community - Muhammad Fiqih Cholidi; Abdul Hannan Ar-Rifa’i (AL QUDS : Jurnal Studi Alquran dan Hadis, 2026)
The emergence of the Muslim middle class in contemporary times faces epistemological and structural challenges, mainly due to the colonial period that reinforced Western epistemology and sidelined science-oriented interpretations. Building upon the rationalist foundations laid by earlier reformist exegetes, Tafsir Al-Jawāhir by Ṭanṭāwī Al-Jawhari attempts to explain the relationship between the Qur'an and science, but often faces criticism from traditionalists. Using a qualitative library research approach and analyzing through the lens of the sociology of science, this study examines how scientific interpretation in Tafsir Al-Jawhari can motivate the Muslim middle class as a catalyst for intellectual renewal, while also identifying obstacles to combining science with Islamic studies. This study outlines three main factors: (1) Tafsir Al-Jawhari functions as a scientific encyclopedia that integrates contemporary science with the Qur'an, encouraging a scientific mentality; (2) Analysis of the decline of Islamic science and a call to revitalize the classical Islamic scientific ethos; (3) The function of tafsir in building a scientific tradition within the Muslim community. The findings suggest that scientific interpretation can serve as a catalyst for social and economic transformation within the Muslim middle class, leading them toward the formation of an engaged scientific community. This research is limited in its ability to ascertain the precise background of the Muslim middle class and the acceptance of this view worldwide. Therefore, additional research is recommended to examine scientific interpretation within specific societal frameworks, such as Indonesia, to gain a deeper understanding of its significance.